Mental toughness among rugby referees in Malaysia / Nur Anis Syahidah Abdul Aziz - Abdul Aziz, Nur Anis Syahidah (Faculty of Sport Science and Recreation, 2016)
This study aims to measure and indicate differences in psychological performance on level 1 and level 2 rugby referees in Malaysia. The Psychological Performance Inventory (PPI) (Loehr, 1986) was adopted and used by rugby referees. The total of the subjects for this study are 30 rugby referees (level 1 n=15, level 2 n=15) registered under Malaysia Rugby Union (MRU) body. The psychological performance variables in the questionnaire included self-confidence, negative energy control, attention control, visualization and imagery control, motivation, positive energy and attitude control. The descriptive statistics of the variables of the variables are psychological performance (4.05±0.449). Finding shows there is no significant differences in psychological performance subscales between level 1 and level 2 rugby referees in Malaysia. Level 2 rugby referees scored slightly higher compare to level 1 rugby referees. In conclusion, the psychological skills assessments can enhance Malaysia rugby referees performance and recommends that Malaysia Rugby Union (MRU) can provide long-term development of mental skills among rugby referees in Malaysia. Further studies should be conducted to identify psychology and physical factors that can influence referees performance